1998
DOI: 10.1016/s0306-4522(97)00394-1
|View full text |Cite
|
Sign up to set email alerts
|

Increasing age reduces expression of long-term depression and dynamic range of transmission plasticity in CA1 field of the rat hippocampus

Abstract: Abstract--Long-term depression, depotentiation and long-term potentiation of field excitatory postsynaptic potentials in the CA1 field of the hippocampus were studied in slices from two-, 12-, 24-and 36-week-old rats. Long-term potentiation was induced by stimulating afferent fibres for 1 s at 100 Hz. Long-term depression was induced either by stimulating the afferent pathways twice for 15 min at 1 Hz (protocol 1), giving in total 1800 pulses, or by stimulating the fibres at 5 min intervals twice at 1 Hz for 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 55 publications
1
14
0
Order By: Relevance
“…Under our experimental conditions, the amount of LTD induced by 1 Hz stimulation was not different between young and aged rats in agreement with other studies indicating no change in LTD during aging (Kumar & Foster, 2007;Billard, 2010;Kollen et al 2010). However, others demonstrate an enhanced (Norris et al, 1996;Kumar & Foster, 2005) or a decreased susceptibility to LTD either in middleaged (Kamal et al, 1998) or aged animals (Lee et al, 2005). These discrepancies result from differences in methodology, including age, strain of the animals and the Ca ⁄ Mg ratio of the recording solution.…”
Section: Discussionsupporting
confidence: 88%
“…Under our experimental conditions, the amount of LTD induced by 1 Hz stimulation was not different between young and aged rats in agreement with other studies indicating no change in LTD during aging (Kumar & Foster, 2007;Billard, 2010;Kollen et al 2010). However, others demonstrate an enhanced (Norris et al, 1996;Kumar & Foster, 2005) or a decreased susceptibility to LTD either in middleaged (Kamal et al, 1998) or aged animals (Lee et al, 2005). These discrepancies result from differences in methodology, including age, strain of the animals and the Ca ⁄ Mg ratio of the recording solution.…”
Section: Discussionsupporting
confidence: 88%
“…It is worth noting that VGCC activation is not related to memory acquisition, but only to the retention of information (Borroni et al, 2000) and that the excessive activation of the L-subtype of VGCCs may be detrimental to memory formation (Liu et al, 2003). Furthermore, we have shown that LTP is rapidly depotentiated in adult but not in aged animals, using an LFS protocol (Kamal et al, 1998). Since LTP saturation disrupts memory formation in young rats (Moser and Moser, 1999), a reduced capacity of hippocampal networks to be reset from potentiated levels may also constitute a synaptic mechanism contributing to cognitive aging.…”
Section: Discussionmentioning
confidence: 99%
“…This finding appears to raise a possibility that prenatal exposure to morphine could significantly alter cytosolic downstream mechanisms, such as protein phosphatases that were important for the expression of LTD (Malenka, 1994). In addition, the magnitude of LTP and LTD and/or depotentiation can be seen as reflecting the dynamic range of long-term modulation of transmission strength in glutamatergic synapses (Baskys and Malenka, 1991;Kamal et al, 1998). This dynamic range may be of significance for information processing by the hippocampus.…”
Section: Yang Et Almentioning
confidence: 98%